The Effectiveness of the promotional mix elements in customer perception of the value "study of a sample of customers Mobilis"of the product - Charef, Ouahiba (Finance and Business Economies Review, 2020)
The objective of this study is to define the role of promotional mix in recognizing the customer value of the product in the telecommunications sector, by identifying the point of view of the study sample members regarding to the promotion of the institution of the product or service (advertising, personal selling, sales promotion, public relations) sothat the customer understands the value of what they offer. To achieve the study objectives, the researcher chose the analytical descriptive method. The researcher also prepared a survey tool to collect data from the study sample, who were selected using a comprehensive intentional method SPSS was also used for data processing and analysis of sample members responses. The study concluded that the use of the promotional mix significantly In customer perception of the value of telecom services in Mobilis. In light of the findings of the study, a number ofrecommendations have been made. The most important of these recommendations areTaking advantage of technological developments to expand promotional mix elements in the marketing communication services.